Upaya Penyelesaian Konflik Kepemilikan Pura dan Kuburan Antara Desa Adat Kemoning dan Desa Adat Budaga - Bayu Adhinata; Komang Ema Marsitadewi (Universitas Negeri Surabaya, 2022)
This study aims to identify and explain the forms of conflict resolution in the ownership of the Dalem Temple and the Graveyard involving two neighboring traditional villages, namely the Kemoning Traditional Village and the Budaga Traditional Village. This study uses a qualitative method with a case study approach. Data in the study was obtained through in-depth interviews with several informants. The informants who became the source of data in this study were five people, namely two key informants, namely the Head of the Traditional Village from Kemoning and Budaga, one informant from the Klungkung Resort Police, and two people from the communities of these two traditional villages. This study found at least four forms of conflict resolution efforts undertaken to resolve this problem, namely negotiation, facilitation, mediation, and arbitration. The final decision in this conflict is determined through an arbitration mechanism involving a customary dispute resolution institution. The use of arbitration is because no definitive agreement has been reached that satisfies both parties through previous negotiations. In the end, the decision of the customary dispute-determination institution is the final decision on the existence of Pura Dalem and the Graveyard, which is the object of dispute in this conflict and must be accepted and carried out by both parties.